Comparison of synchronisation protocols on pregnancy rate in dairy cows and heifers: A systematic review and network meta-analysis - Ambarcioglu, P; Mavridis, D; Yazlik, MO; Vural, R; Akcil Ok, MM; Gürcan, S (Journal of the Hellenic Veterinary Medical Society, 2023)
Estrus synchronisation protocols are used as an essential strategy in the reproductive management of dairy herds, including Ovsynch, Presynch, Selectsynch, Heatsynch, Cosynch, Double-Ovsynch, and some other combinations of these, while the optimal protocol is still uncertain. We performed a network meta-analysis (NMA) to compare the efficacy of the synchronisation protocols in dairy cows and heifers. Pubmed, Scopus, Web of Science, Cabi Direct, and The Cochrane Library were searched up to May 13, 2019. The comparison of synchronisation protocols in terms of pregnancy rate was done by combining direct and indirect evidence. Ranking the synchronisation protocols were conducted by using surface under the cumulative ranking curve (SUCRA). 48 randomized trials involving 9 different protocols were included. Compared with the control group, none of the synchronisation protocols were more effective in pregnancy rate at first insemination. Presynch+Ovsynch was found to be more efficient than Ovsynch (RR=1.21, 95% CI:1.04-1.40), also Presynch+Ovsynch and Presynch+Heatsynch were superior to Presynch+Selectsynch (RR=2.01, 95% CI: 1.03-3.93 and RR=1.91, 95% CI: 1.21-3.01). In conclusion, presynchronisation strategies such as Presynch+Ovsynch increase the effectiveness of pregnancy rate at first insemination related to other synchronisation protocols. Nevertheless, the non-superiority of the synchronisation protocols against not applying any hormonal treatments should be considered in reproductive management in dairy herds.